Evaluation of rhizospheric and endophytic Bacillus spp. and fluorescent Pseudomonas spp. isolated from Theobroma cacao L. for antagonistic reaction to Phytophthora palmivora, the causal organism of black pod disease of cocoa - Thomas, Litty; Gupta, Alka; Gopal, Murali; ChandraMohanan, R.; George, Priya; V. Thomas, George (Journal of Plantation Crops, 2011)
Biological control has assumed significance in the research programmes on disease management of cocoa due to the increasing concern on the detrimental effect of agrochemicals on environment and the presence of residues in food products. This study was conducted to evaluate the potential of Bacillus spp. and fluorescent Pseudomonas spp. isolated from cocoa roots and rhizosphere for their antagonistic reaction against Phytophthora palmivora (Butl.) Butl., causing black pod disease of cocoa. A total of 519 isolates obtained from the rhizosphere and roots of cocoa trees in different locations in South India were evaluated for their antagonistic reaction to P. palmivora, under in vitro conditions on Carrot Dextrose Agar (CDA). Out of the 519 cocoa isolates (359 Bacillus spp. and 160 fluorescent Pseudomonas spp.), 95 isolates (44 rhizospheric and 45 endophytic Bacillus spp; and 6 rhizospheric fluorescent Pseudomonas spp.) were found to be antagonistic to P. palmivora. Four Bacillus spp., one from Pollachi (Bacillus sp. PSB6) and three from Kasaragod (Bacillus sp. KGSB5, Bacillus sp. KGSB11 and Bacillus sp. KGSB26) effected a maximum of 57 % mycelial growth reduction of the fungal pathogen. None of the endophytic fluorescent Pseudomonas spp., showed antagonism against the black pod pathogen. Bacillus spp. isolated from Tamil Nadu showed higher antagonistic potential (48 % of rhizospheric and 76 % of endophytic Bacillus spp.) than bacterial isolates obtained from other states. Further studies with these antagonists showed that 35 %, 18 %, and 56 % of the isolates produced siderophore, HCN and antibiotics respectively. The isolates showing antagonistic activity (89 Bacillus spp. and 6 Pseudomonas spp.) against the fungal pathogens can be used in developing bio-control agents.